Cs sorption of Mn–Fe based Prussian blue analogs with periodic precipitation banding in agarose gel. Issue 16 (6th April 2022) - Hayashi, Hisashi
Abstract : The Cs sorption capacity of Mn–Fe PBA precipitates (spontaneously formed in agarose gel) increased over time. During the Cs sorption, periodic precipitation bands comprising large crystallites were generated, suggesting the contribution of Ostwald ripening. Abstract : We report the understanding of Cs sorption/desorption properties of Mn–Fe based Prussian blue analogs (Mn–Fe PBA) and Prussian blue (PB) in agarose gel via X-ray fluorescence spectroscopy and scanning electron microscopy. After contacting a 2 mass% agarose gel containing 100 mmol dm −3 [Fe(CN)6 ] 3− ions (inner electrolyte gel) with a 1 mass% agarose gel containing 550 mmol dm −3 Mn 2+ or Fe 2+ ions (outer electrolyte gel) in a plastic straw for 11 days, the clipped 10 mm-long gel columns of uniformly formed precipitates (named "Mn–Fe PBA gel" and "PB gel") were used to investigate their Cs sorption/desorption properties. The Mn–Fe PBA gel showed several interesting features that were not observed in the PB gel. The Cs sorption capacity of the Mn–Fe PBA gel increased over time, and after ∼1200 h reached a value comparable to the most optimal values previously reported. During Cs sorption, Mn 2+ ions were constantly released from the Mn–Fe PBA gel, and several periodic precipitation bands were generated. The positions of the periodic bands agreed with those of the peak distributions of Cs, Mn, and Fe, suggesting that the concentration fluctuation of Mn II –Fe III PBA in the gel resulted in the periodic band formation. In these bands, large crystallites (>10 μm) were dominant, suggesting the contribution of Ostwald ripening. During Cs desorption, while Mn 2+ ions were released from the Mn–Fe PBA gel, the release of Cs + ions was considerably suppressed (∼1/3 for the PB gel). Based on these results, a model for Cs sorption by the Mn–Fe PBA gel was proposed, and its potential applications were discussed.